2022
DOI: 10.1038/s41467-022-33064-8
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of poly(butylene succinate) in soil laboratory incubations assessed by stable carbon isotope labelling

Abstract: Using biodegradable instead of conventional plastics in agricultural applications promises to help overcome plastic pollution of agricultural soils. However, analytical limitations impede our understanding of plastic biodegradation in soils. Utilizing stable carbon isotope (13C-)labelled poly(butylene succinate) (PBS), a synthetic polyester, we herein present an analytical approach to continuously quantify PBS mineralization to 13CO2 during soil incubations and, thereafter, to determine non-mineralized PBS-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 88 publications
2
18
0
Order By: Relevance
“…LDPE fragments persisted by our methods (Figure S6), and again field tests confirmed that assessment. , Fragments from incomplete degradation generated due to inappropriate processing, especially too short aerobic residence time in anaerobic/aerobic processes, may enter agricultural fields. For the present case in that scenario, continued biodegradation in soil is expected due to the measured identity of partially degraded fragments (Figure a,b). , One can envision a follow-up investigation of particulate and nonparticulate polymer fractions by NMR, potentially supported by methods detecting isotopically labeled monomers. , Furthermore, fragmentation kinetics must be investigated in relation to copolymer composition, composting conditions, plastic shape, and up to entire bags and cups. Specifically, it has to be verified if the correlation of fragmentation kinetics with CO 2 evolution (Figure ) also holds for 25 μm thin films (in bags) or coatings (on paper cups).…”
Section: Environmental Implicationsmentioning
confidence: 89%
“…LDPE fragments persisted by our methods (Figure S6), and again field tests confirmed that assessment. , Fragments from incomplete degradation generated due to inappropriate processing, especially too short aerobic residence time in anaerobic/aerobic processes, may enter agricultural fields. For the present case in that scenario, continued biodegradation in soil is expected due to the measured identity of partially degraded fragments (Figure a,b). , One can envision a follow-up investigation of particulate and nonparticulate polymer fractions by NMR, potentially supported by methods detecting isotopically labeled monomers. , Furthermore, fragmentation kinetics must be investigated in relation to copolymer composition, composting conditions, plastic shape, and up to entire bags and cups. Specifically, it has to be verified if the correlation of fragmentation kinetics with CO 2 evolution (Figure ) also holds for 25 μm thin films (in bags) or coatings (on paper cups).…”
Section: Environmental Implicationsmentioning
confidence: 89%
“…By coopting their repertoire of degradative traits 78,80 to modify or degrade polymer components (i.e., 'exaptative plastibiome'), these pathogens may facilitate co-colonisation, co-degradation and co-metabolisation of MP by other members of the community, as previously described for other substrates 81,82 , ultimately enabling plasticlastic commensalism and syntrophy. It has been shown that some microbes can completely degrade, assimilate, and mineralise at least certain plastics under experimental conditions [83][84][85] , a feat that is yet to be observed in nature. The coselection of fungi into the plastisphere based on their biodegradability may indicate that fungal metabolism has already become better adapted to plastic polymers.…”
Section: Discussionmentioning
confidence: 99%
“…PBS is a highly biodegradable polymer. It is used not only for “green” packaging but also for in many biomedical application [92,93] . Its decomposition can be either hydrolytic or enzymatic.…”
Section: Synthesis Of Biodegradable Polymers From Propylenementioning
confidence: 99%
“…It is used not only for "green" packaging but also for in many biomedical application. [92,93] Its decomposition can be either hydrolytic or enzymatic. Depending on its chemical composition and conditions (e.g., pH, temperature), its half-life can vary in a wide range.…”
Section: General Synthesis Of Pbs Pbat and Pbc Polymersmentioning
confidence: 99%